Recent advances in honey-based nanoparticles for wound dressing: a review - Bahari, Norfarina; Hashim, Norhashila; Md Akim, Abdah; Maringgal, Bernard (MDPI, 2022)
Wounds with impaired healing, including delayed acute injuries and chronic injuries, generally fail to progress through normal healing stages. A deeper understanding of the biochemical processes involved in chronic wound cures is necessary to correct the microenvironmental imbalances in the wound treatment designs of products. The therapeutic benefits of honey, particularly its antimicrobial activity, make it a viable option for wound treatment in a variety of situations. Integration with nanotechnology has opened up new possibilities not only for wound healing but also for other medicinal applications. In this review, recent advances in honey-based nanoparticles for wound healing are discussed. This also covers the mechanism of the action of nanoparticles in the wound healing process and perspectives on the challenges and future trends of using honey-based nanoparticles. The underlying mechanisms of wound healing using honey are believed to be attributed to hydrogen peroxide, high osmolality, acidity, non-peroxide components, and phenols. Therefore, incorporating honey into various wound dressings has become a major trend due to the increasing demand for combination dressings in the global wound dressing market because these dressings contain two or more types of chemical and physical properties to ensure optimal functionality. At the same time, their multiple features (low cost, biocompatibility, and swelling index) and diverse fabrication methods (electrospun fibres, hydrogels, etc.) make them a popular choice among researchers.